Sixth national survey of pesticides in groundwater in New Zealand - ME Close; A Skinner (New Zealand Journal of Marine and Freshwater Research, 2012)
The 2010 4‐yearly national survey of pesticides in groundwater included 162 wells. The aims of the survey were to update the national overview of pesticides in New Zealand's groundwater systems, to investigate temporal variation in pesticide concentrations between surveys, and to identify environmental factors associated with pesticide contamination. Pesticides were detected in 38 wells (23%), with two or more pesticides detected in 15 wells (9%). Pesticides were measured in wells in nine of the 14 regions sampled. One well showed a dieldrin concentration greater than the maximum acceptable value for drinking water. A total of 22 different pesticides were detected. Herbicides were the most common pesticide group detected. Levels of only three of the 66 pesticide detections exceeded 1 mg/m 3 . Comparisons with earlier surveys indicate that a similar percentage of wells had detectable pesticides in the last four surveys once correction for variable detection limits was made.